2001
DOI: 10.1007/s003400100549
|View full text |Cite
|
Sign up to set email alerts
|

Ambient formaldehyde detection with a laser spectrometer based on difference-frequency generation in PPLN

Abstract: A laser spectrometer based on difference-frequency generation in periodically poled LiNbO3 (PPLN) has been used to quantify atmospheric formaldehyde with a detection limit of 0.32 parts per billion in a given volume (ppbV) using specifically developed data-processing techniques. With state-of-the-art fiber-coupled diode-laser pump sources at 1083 nm and 1561 nm, difference-frequency radiation has been generated in the 3.53-micrometers (2832-cm-1) spectral region. Formaldehyde in ambient air in the 1- to 10-ppb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(22 citation statements)
references
References 0 publications
2
19
0
Order By: Relevance
“…This model has been designed by Weinstein and colleagues (13) that determines the changes in drug users' possible high risk behaviors and shows the probability of transmitting infection. The input data used in the model were collected by self-reported method from 259 IDUs in seven governmental MMT centers in Shiraz, south of Iran (Table 1).…”
Section: Methodsmentioning
confidence: 99%
“…This model has been designed by Weinstein and colleagues (13) that determines the changes in drug users' possible high risk behaviors and shows the probability of transmitting infection. The input data used in the model were collected by self-reported method from 259 IDUs in seven governmental MMT centers in Shiraz, south of Iran (Table 1).…”
Section: Methodsmentioning
confidence: 99%
“…In order to determine the integrated absorbance A I (the area under the absorption line profile), absorption spectra were fitted to Voigt [32] and Galatry [33] profiles, using a Levenberg-Marquardt multi-line fitting algorithm. In the fit procedure, the baseline approximated with a 4th-order polynomial was experimentally found to well represent laser power ramp, allowing good removal of the variation of laser power in the fitted residual.…”
Section: Data Processing and Retrievalsmentioning
confidence: 99%
“…For example, Rehle et al [7] reported formaldehyde detection at 0.32 ppb using a 353 nm laser, and Richter et al [8] achieved a limit of detection of 74 ppt at 3.5 µm, but with a longer response time (1 minute rather than a few seconds). TDLS systems demonstrate good gas selectivity and signal-to-noise ratios, but are relatively expensive and complex to manufacture.…”
Section: Introductionmentioning
confidence: 97%